Buitenzorg and surrounding gardens (Bulletin KNOB, 1999)
In 1745 the first House of Buitenzorg was founded in the Dutch East Indies, situated at the present Bogor near Jakarta (Indonesia). Governor-General G.W. Baron van Imhoff was the commissioner. This house and its successors (after fire and earthquake) and the surrounding park are depicted on numerous drawings, prints and paintings. Little is known about the landscape gardening around the house before 1817.Just one single drawing (1772) by Johannes Rach gives an impression of the first gardens. The garden consists of l) a formal front garden constituted by hedges; 2) a shady middle garden around Post Philippina; 3) geometrical 'parterres de broderie', linking up with the main buildings and the promenade; 4) wood plantation behind the promenade, closed off by a row of palms; 5) and finally an orchard, annex menagerie at the side.From north to south the character of the gardening style changes from formally geometrical to more scenic and natural. The character of the layout clearly has a utility function (orchards, shady marketplace, and possibly a coffee, tea and coconut plantation) and an aesthetic function (special hedge garden and parterres de broderie, both symmetrical in layout).It looks as if Buitenzorg thus served as a model for agricultural and horticultural projects in this region. After 1817 the garden was changed and expanded to 's Lands Plantentuin (National Botanical Garden) or in Indonesian Kebun Raya, one of the largest and best-known tropical botanical gardens in the world. This latter function of botanical garden was completely in line with the scheme laid out by the commissioner of the first house of Buitenzorg, Baron van Imhoff.